Performance of waste insulating mineral oil-based biodiesel in a direct-injection CI engine - Sivakumar, A.; Sathiyamoorthi, R.; Jayaseelan, V.; Gandhi, R. Ashok; Sudhakar, K. (Universiti Malaysia Pahang, 2019)
Mineral oil has been used as an insulating fluid in the power industry. However, surplus waste oil poses serious environmental threats because of disposal concerns. Waste to biofuel is an excellent way to deal with waste material from various sources. In this study, the trans-esterification method was utilised to convert the waste-insulating mineral oil into a quality bio-fuel. Waste-insulating transformer oil was converted to biodiesel, and it was tested according to ASTM standards. Four different blends of waste-insulating biodiesel with diesel in 25 per cent (WIOBD25), 50 per cent (WIOBD50), 75 per cent (WIOBD75), and 100 per cent fractions (WIOBD100), were used for performance testing in a direct injection compression ignition (DICI) engine. The combustion parameters such as BSFC, EGT, and BTE were evaluated with varying crank angles and constant engine speed. The waste-insulating biodiesel performance results are then compared with diesel fuel. BSFC increased as the biofuel mixture in diesel was raised, and the brake thermal efficiency (BTE) was significantly reduced compared to diesel for all WIOBD diesel mixtures. Due to the combustion process, a high pressure and heat release rate (HRR) were noticed inside the cylinder with the waste-insulating oil-derived biodiesel samples. WIOBD biodiesel blends produced lower levels of hydrocarbon, carbon monoxide, and smoke emissions than diesel fuel, but greater levels of nitrogen oxides (NOx) were produced than diesel fuel. In addition to lower emissions combined with improved engine performance, the WIOBD25 fuel blend has been found to be experimentally optimal for practical application. As a result, the test findings indicated that WIOBD biodiesel might be used as a substitute for conventional diesel fuel.